Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-29490-8
|View full text |Cite
|
Sign up to set email alerts
|

Three newly identified Immediate Early Genes of Bovine herpesvirus 1 lack the characteristic Octamer binding motif- 1

Abstract: Only three immediate early genes (IE) BICP0, BICP4 and BICP22 of Bovine herpesvirus 1 (BoHV-1) are known. These genes are expressed coordinately and their promoters are well characterized. We provide evidence for expression of three additional IE genes of BoHV-1 i.e. UL21, UL33 and UL34. These genes are expressed in the presence of cycloheximide (CH) at the same time as known IE genes. Surprisingly, the promoters of newly identified IE genes (UL21, UL33, UL34) lack the OCT-1 binding site, a considered site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(56 reference statements)
0
4
1
Order By: Relevance
“…We can only speculate that the 100 mg/mL CHX concentration may have been insufficient for completely blocking the transcription of ul54 gene, or conceivably the tegument bICP4 transactivator was able to induce the observed low-level expression from this gene (BoHV-1 bICP4 transactivator has also been shown to be present in the viral tegument [80]). Pokhriyal and colleagues [81] have reported the identification of three additional IE genes (ul21, ul33, and ul34), however, we could not confirm this result. We assume that the authors might have applied inadequate amount of CHX for the infected cells.…”
Section: Discussioncontrasting
confidence: 88%
“…We can only speculate that the 100 mg/mL CHX concentration may have been insufficient for completely blocking the transcription of ul54 gene, or conceivably the tegument bICP4 transactivator was able to induce the observed low-level expression from this gene (BoHV-1 bICP4 transactivator has also been shown to be present in the viral tegument [80]). Pokhriyal and colleagues [81] have reported the identification of three additional IE genes (ul21, ul33, and ul34), however, we could not confirm this result. We assume that the authors might have applied inadequate amount of CHX for the infected cells.…”
Section: Discussioncontrasting
confidence: 88%
“…The studies 38 have shown that the BoHV-1 genome is GC-rich, with SP1 consensus binding sites and other GC-rich Moines, which may promote binding to specific KLF transcription factors and stimulate viral transcription early in latency reactivation. 4 In the KEGG pathway, these DEGs were mostly enriched in the proteoglycans in cancer, cytokine-cytokine receptor interaction and viral carcinogenesis, mitogen-activated protein kinase and calcium signaling pathway. MAPK signaling pathways play an important role in pathogen–host interaction, some viruses such as Epstein-Barr virus (EBV) and herpes simplex virus (HSV) affect host cell survival or cell cycle or viral replication or alter immune responses by MAPK-ERK cascade.…”
Section: Discussionmentioning
confidence: 99%
“… 2 The genome of BoHV-1 is about 135 KB, its diameter of virus particles is about 150 to 220 nm, enabling it to invade mucosal epithelial cells of the upper respiratory tract and those of the reproductive tract of cattle and proliferate in large numbers at the site of infection, resulting in cytopathic effects (CPE). 3 BoHV-1 mainly infects cattle and causes respiratory and reproductive diseases and is associated with other clinical symptoms and systemic diseases of newborn calves, 4 which causes significant economic losses to beef and dairy cattle industry all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…The products of the first three serve as activators for all viral promoters, (Saydam et al , 2004(Saydam et al , , 2006 while the function of CIRC, which translates into a small, myristylated protein is unclear (Fraefel, Ackermann and Schwyzer, 1994) . Recently, Pokhriyal et al (Pokhriyal et al , 2018) found that three other genes (ul21, ul33 and ul34) are also expressed during the IE phase of the infection in cycloheximide-treated cells. These genes have a TATA box but lack the OCT-1 binding site characteristic of conventional IE genes.…”
Section: The Bohv-1mentioning
confidence: 99%
“…We also detected this previously annotated isoform, although in very low abundance. Pokhriyal et al reported (Pokhriyal et al , 2018) the immediate early expression of three genes (ul21, ul33 and ul34) ought to be thought late. We could detect two of these (ul33 and ul34) to exhibit an early expression pattern, and in addition, found that 41 out of the 69 analysed genes are already expressing at 2h p.i., however, 66 only reach their maximum abundance following replication, suggesting that some early genes benefit from the onset of DNA replication.…”
Section: Gene Expression Analysis During Lytic Infectionmentioning
confidence: 99%